Imaging and visualization of 3-D cardiac electric activity. - Bin He
Noninvasive imaging of cardiac electric activity is of importance for better understanding of the underlying mechanisms and for aiding clinical diagnosis and intervention of cardiac abnormalities. We propose to image the 3D cardiac bioelectric source distribution from body-surface electrocardiograms. Cardiac electrical sources were modeled by a current dipole distribution throughout the entire myocardium, and estimated by using the Laplacian weighted minimum norm (LWMN) algorithm from body-surface potentials. The estimated inverse solution of the current distribution was further improved by using a recursive weighting strategy for localized sources, such as origins of cardiac arrhythmias. Computer simulations were conducted to test the feasibility of the proposed approach by using a 3D ventricle model embedded in a realistically shaped torso model. The boundary element method was used to solve the forward problem from assumed cardiac sources to the body-surface potentials. Two test dipoles were placed in the left and right ventricles, simulating the early activation associated with ventricular arrhythmias. The LWMN inverse solution showed an equivalent source distribution over both ventricles, with spread areas of activity overlying the positions of the test dipoles. The sharpened inverse image provides well-localized focal sources near the test dipole positions. In summary, the presented computer simulation suggests that the proposed 3D cardiac current source imaging and localization approach appears to be a promising candidate for localizing and imaging sites of origins of cardiac activation.
Keywords: 3D cardiac bioelectric source distribution; 3D cardiac electric activity visualization; 3D ventricle model; Laplacian imaging; Laplacian weighted minimum norm algorithm; Body-surface ECG; Body-surface potentials; Boundary element method; Cardiac abnormalities; Cardiac arrhythmia; Catheter ablation; Clinical diagnosis; Clinical intervention; Computer simulations; Current dipole distribution; Dipoles; Early cardiac activation; Electrocardiography; Inverse solution; Localized focal sources; Localized sources; Myocardium; Noninvasive imaging; Recursive weighting strategy; Sharpened inverse image; Torso model